FORMATION OF THE READINESS OF MASTERS FOR THE DEVELOPMENT OF ECOLOGICAL CULTURE OF PEOPLE WITH LIMITED ABILITIES BY MEANS OF THE MUSEUM - Larisa A. Kolyvanova; Tamara M. Nosova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the professional education of masters in the direction 44.04.01 - Pedagogical education («Biological education») at natural and geographical faculty of PGSGA, in order to form the readiness for the training of physically disabled people. Training of teachers in a magistracy is a topical issue today due to the strategy of modernization of pedagogical education. The new content of the practical training of teachers according to the main professional educational program is directed at the development of the main competences specified in the professional standard. According to the main educational program representing a set of the normative and educational and methodical documents defining the purposes, the contents, conditions and technologies of realization of the process of training and education, the expected results, an assessment of quality of training of masters, the basis of formation of professional and common cultural competence of masters is formed. The main types of vocational training of undergraduates are: pedagogical, designing, methodical, administrative cultural and educational, research activity focused on the requirements of labor market. Thus, it is important that in the course of professional education of the future expert the skills of training of persons with limited opportunities of health directed at the formation of bioecological literacy of the students and their health and safety were created. The essential role in environmental protection, ecological education, formation of ecological culture of people with special educational needs is played by the museums whose main objective of work consists in the development of the identity of the person, his cultures, consciousness and thinking, carried out by museum means. In the conditions of modernization the museum carries out functions of the educational center and updates the content of biological and ecological education.